2023
DOI: 10.3389/fpsyg.2023.1196274
|View full text |Cite
|
Sign up to set email alerts
|

Writing motivation and ability profiles and transition during a technology-based writing intervention

Abstract: Students exhibit heterogeneity in writing motivation and ability. Profiles based on measures of motivation and ability might help to describe this heterogeneity and better understand the effects of interventions aimed at improving students’ writing outcomes. We aimed to identify writing motivation and ability profiles in U.S. middle-school students participating in an automated writing evaluation (AWE) intervention using MI Write, and to identify transition paths between profiles as a result of the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Previous research has elaborated on the potential contribution of the machine to students' autonomy in learning (Nova, 2018;Umamah & Cahyono, 2022). Indeed, recent experiments confirm an increase in students' goal calibration, confidence in writing, and self-efficacy (Cruz Cordero et al, 2023;Wilson et al, 2023).…”
Section: Positive Perspective Of Awementioning
confidence: 93%
See 1 more Smart Citation
“…Previous research has elaborated on the potential contribution of the machine to students' autonomy in learning (Nova, 2018;Umamah & Cahyono, 2022). Indeed, recent experiments confirm an increase in students' goal calibration, confidence in writing, and self-efficacy (Cruz Cordero et al, 2023;Wilson et al, 2023).…”
Section: Positive Perspective Of Awementioning
confidence: 93%
“…Also, since AWE generates form-focus feedback, it is suggested that AWE should be utilized as an addition to teaching and peer feedback (Bayerlein, 2014;Engeness, 2018;Xu & Zhang, 2022). However, recent experiments show that AWE integration promotes students' self-regulation, especially self-efficacy, attitude, and motivation toward writing and goal calibration (Cruz Cordero et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%
“…The present study examines comments provided by students in Grades 7 and 8 who were given access to an AWE system called MI Write in the context of a randomized controlled trial (RCT). Conducted during the 2021–2022 school year, the RCT examined the efficacy of MI Write on students’ writing outcomes (see [ 33 ]).…”
Section: Methodsmentioning
confidence: 99%